2005
DOI: 10.1128/jb.187.1.376-381.2005
|View full text |Cite
|
Sign up to set email alerts
|

The katA Catalase Gene Is Regulated by OxyR in both Free-Living and Symbiotic Sinorhizobium meliloti

Abstract: The characterization of an oxyR insertion mutant provides evidences that katA, which encodes the unique H 2 O 2 -inducible HPII catalase, is regulated by OxyR not only in free-living Sinorhizobium meliloti but also in symbiotic S. meliloti. Moreover, oxyR is expressed independently of exogenous H 2 O 2 and downregulates its own expression in S. meliloti.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…In silico sequence analysis performed by us indicated that R. leguminosarum strains usually contain one housekeeping chromosomal gene and one to two genes located on plasmids that encode catalases. Jamet et al (2003Jamet et al ( , 2005 have indicated that S. meliloti possesses three distinct catalases: two monofunctional KatA and KatC enzymes and one bifunctional catalase-peroxydase KatB. The katB gene is constitutively expressed during bacterial growth in the culture and is not expressed under oxidative stress conditions, whereas the expression of the katA and katC genes was induced in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In silico sequence analysis performed by us indicated that R. leguminosarum strains usually contain one housekeeping chromosomal gene and one to two genes located on plasmids that encode catalases. Jamet et al (2003Jamet et al ( , 2005 have indicated that S. meliloti possesses three distinct catalases: two monofunctional KatA and KatC enzymes and one bifunctional catalase-peroxydase KatB. The katB gene is constitutively expressed during bacterial growth in the culture and is not expressed under oxidative stress conditions, whereas the expression of the katA and katC genes was induced in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, KatA activity is upregulated in the sitA:mTn5 mutant. KatA is controlled by the global sensor of H 2 O 2 stress, OxyR (27). Upregulation of KatA suggests that even during normal growth, the sitA::mTn5 mutant experiences an increased intracellular stress from reactive oxygen species.…”
Section: Resultsmentioning
confidence: 99%
“…Several genes known to be required for defense against ROS in the free-living state are dispensable for symbiosis. For example, disruption of the global regulator of H 2 O 2 protection, oxyR, makes the freeliving strain extremely sensitive to H 2 O 2 but does not affect symbiosis (27).…”
mentioning
confidence: 99%
“…However, the level of stress experienced by bacteria in the infection thread due to ROS is unknown. Single mutants in any of the three S. meliloti catalases, one of the two superoxide dismutases (sodB) or in the global regulator of H 2 O 2 protection, oxyR, are sensitive to ROS, but are not defective in symbiosis [53][54][55][56] . However, double mutants in the genes encoding catalase B and catalase C (katB/katC) or catalase A and catalase C (katA/katC) are compromised in their ability to invade the host plant 53,54 .…”
Section: Sinorhizobium Meliloti Succinoglycan Biosynthesismentioning
confidence: 99%